Attitude, parental encouragement and perception of the importance of English in English language learning. - A survey amongst form six students in Marang district, Terengganu / Zafri Abdul Kadir - Abdul Kadir, Zafri (2012)
This study investigated the students' perception of the importance of English language amongst a sample of 150 Upper Six students from a population of 755 students from six schools in the district of Marang, Terengganu. Also studied was whether their attitude towards learning English language is positive and whether they receive sufficient parental encouragement and support in their English language learning. It was found that the students were well aware of the importance of English language and also had a very positive attitude towards English Language learning. The parental encouragement and support scores also recorded a high total mean. In all three instances the sample means were well above the mid-point means indicating that the sample means fell in the higher halves of the mean scores. This implies that students are well aware of the importance of English language, are very positive about learning English language and receive more than adequate parental encouragement and support in their English language learning. Correlation analysis showed that there was a significant and positive relationship between the students' perception of the importance of English language and their attitude towards learning the language. Since the students' attitude and parental encouragement and support seem to be satisfactory, future researchers should investigate whether the curriculum offered is suitable for rural students.